ナンキョクサン ノ サカナ Notothenia neglecta Nybelin (ノトセニア カ) モウマク ノ ヒカリ ジュヨウ サイボウ ト シキソ ジョウヒ ノ ビサイ コウゾウ - Donatti, Lucelia; Fanta, Edith (2002)
P(論文) 南極産の魚Notothenia neglectaはキングジョージ島, アドミラルティ湾の生息域では優先的に出現する魚である。本種は捕食者であり, しばしば, 正確な視覚を用いた待ち伏せ採餌を行う。そこで網膜の光受容細胞と色素上皮の微細構造を電子顕微鏡を用いて解析することとした。網膜には色素上皮と桿体, 短い独立型錐体, 長い独立型錐体, 不等双子型錐体, 三子型錐体の5種の光受容細胞とニューロン, 支持細胞が存在する。色素上皮はたたみ込まれた基底膜, 基底ミトコンドリア, 平滑な網状体, 大量の微小管, メラニン顆粒, 食作用胞, 光受容細胞の剥離膜で特徴づけられている。錐体には外節の二重膜状板, 楕円体・筋様体の副錐体, 連結繊毛, 微絨毛が, 楕円体中には中心小体, そして筋様体・楕円体域には掌状筋様体, ミューラー細胞の頂上微絨毛が存在する。これら総ての状態は, N. neglectaに環境の光条件の変化に対するあらゆる種類の適応を可能にし, N. neglectaを, 水平, 垂直方向に調整可能な10層に配置された細胞を持つという, 複雑な網膜を備える魚類の1種としている。このことが, 周年, 充分な視覚による行動と餌と環境との認知を可能にしているのである。 The Antarctic nototheniid Notothenia neglecta is the dominant fish in its habitat in Admiralty Bay, King George Island. They are predators, often ambush feeders, with accurate visual behaviour. For that reason, the ultrastructure of retinal photoreceptive cells and the pigment epithelium was analysed through electron microscopy. Their retina has a pigment epithelium, five different photoreceptors : rods, short single, long single, double, and triple cones, and neurones and support cells. The pigment epithelium is characterised by infoldings of the basal membrane, basal mitochondria, smooth reticule, large amount of microtubules, melanin granules, phagosomes and detached membranes of photoreceptors. Cones show bimembranous discs in the outer segment, an accessory outer segment, a connecting cilium, calycal processes, microtubules in the inferior ellipsoid and myoid, centrioles in the ellipsoid, interdigitating myoid fins and apical microvilli of Muller cells in the myoid and elliposid region. All these features allow all sorts of adaptations to the environmental photic variations, and situate N. neglecta among fish with a complex retina, with cells that are arranged in ten layers, allowing horizontal and vertical integration among them. This allows optimal visual behaviour and perception of food and environment in every Antarctic season. departmental bulletin paper